TetR-like regulator BP1026B_II1561 controls aromatic amino acid biosynthesis and intracellular pathogenesis in Burkholderia pseudomallei - McMillan, Ian A.; Norris, Michael H.; Heacock-Kang, Yun; Zarzycki-Siek, Jan; Sun, Zhenxin; Hartney, Brooke A.; Filipowska, Liliana K.; Islam, M. Nurul; Crick, Dean C.; Borlee, Bradley R.; Hoang, Tung T. (Frontiers in Microbiology, 2024)
Burkholderia pseudomallei (Bp) causes the tropical disease melioidosis that afflicts an estimated 165,000 people each year. Bp is a facultative intracellular pathogen that transits through distinct intracellular stages including attachment to host cells, invasion through the endocytic pathway, escape from the endosome, replication in the cytoplasm, generation of protrusions towards neighboring cells, and host cell fusion allowing Bp infection to spread without exiting the intracellular environment. We have identified a TetR-like transcriptional regulator, BP1026B_II1561, that is up-regulated during the late stages of infection as Bp protrudes toward neighboring cells. We have characterized BP1026B_II1561 and determined that it has a role in pathogenesis. A deletional mutant of BP1026B_II1561 is attenuated in RAW264.7 macrophage and BALB/c mouse models of infection. Using RNA-seq, we found that BP1026B_II1561 controls secondary metabolite biosynthesis, fatty acid degradation, and propanoate metabolism. In addition, we identified that BP1026B_II1561 directly controls expression of an outer membrane porin and genes in the shikimate biosynthetic pathway using ChIP-seq. Transposon mutants of genes within the BP1026B_II1561 regulon show defects during intracellular replication in RAW264.7 cells confirming the role of this transcriptional regulator and the pathways it controls in pathogenesis.BP1026B_II1561 also up-regulates the majority of the enzymes in shikimate and tryptophan biosynthetic pathways, suggesting their importance for Bp physiology. To investigate this, we tested fluorinated analogs of anthranilate and tryptophan, intermediates and products of the shikimate and tryptophan biosynthetic pathways, respectively, and showed inhibition of Bp growth at nanomolar concentrations. The expression of these pathways by BP1026b_II1561 and during intracellular infection combined with the inhibition of Bp growth by fluorotryptophan/antranilate highlights these pathways as potential targets for therapeutic intervention against melioidosis. In the present study, we have identified BP1026B_II1561 as a critical transcriptional regulator for Bp